2011
DOI: 10.1007/s10750-011-0953-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bythotrephes longimanus (Crustacea, Cladocera) on the abundance, morphology, and prey community of Leptodora kindtii (Crustacea, Cladocera)

Abstract: We hypothesized that native Leptodora kindtii would be shorter and have smaller feeding baskets in central Ontario lakes with greater abundances of small-bodied zooplankton prey, and that differences in zooplankton size among lakes could be attributed to the invasive cladoceran Bythotrephes longimanus. We evaluated these conjectures by comparing size metrics of Leptodora and the size of their preferred cladoceran prey in lakes invaded or not by Bythotrephes. Leptodora was less abundant in invaded lakes, but we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Rapid developmental times can also establish a large sediment egg bank that provides a constant source of recruitment if thermal conditions change and become less favourable (Walsh et al., 2016). These differences, along with resulting changes in prey community composition and size structure, have contributed to the replacement of Leptodora in lakes invaded by Bythotrephes (Foster et al., 2012; Kerfoot et al., 2016; Lehman & Cáceres, 1993; Weisz & Yan, 2011). Our findings around phenology also add new insights into this process and raise the risk that introduced Bythotrephes might outcompete native predators under a warming climate in relatively cool lakes like Maggiore.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid developmental times can also establish a large sediment egg bank that provides a constant source of recruitment if thermal conditions change and become less favourable (Walsh et al., 2016). These differences, along with resulting changes in prey community composition and size structure, have contributed to the replacement of Leptodora in lakes invaded by Bythotrephes (Foster et al., 2012; Kerfoot et al., 2016; Lehman & Cáceres, 1993; Weisz & Yan, 2011). Our findings around phenology also add new insights into this process and raise the risk that introduced Bythotrephes might outcompete native predators under a warming climate in relatively cool lakes like Maggiore.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that B. longimanus invasion caused declines in L. kindtii abdundance in North America Sprules 2009, Weisz and, as well as a trend for smaller L. kindtii size with increased abundances of invasive B. longimanus (Foster et al 2012). Foster et al (2012) suggest size declines in L kindtii in central Ontario lakes invaded by B. longimanus could be due to direct consumption by B. longimanus, indirect effects of B. longimanus decreasing available zooplankton prey for L. kindtii, and other factors, such as fish predation. They concluded that decreased L. kindtii size was due to competitive effects of B. longimanus predation on small cladocerans.…”
Section: Discussionmentioning
confidence: 93%